Hubungan aktivitas fisik dengan status gizi pada peserta didik SMP - Hullah, Muhammad Rosyad; Punuh, Maureen Irinne; Sanggelorang, Yulianty (Holistik Jurnal Kesehatan, 2025)
Background: Adolescents are a group vulnerable to nutritional problems. The main factor behind this is that adolescence is a period of accelerated growth and development, often accompanied by changes in eating habits and lifestyle. Although each adolescent has different demands, activity levels begin to increase significantly as they approach junior high school. Adolescents' nutritional status is influenced by various factors, including eating habits, economic conditions, cultural background, and physical activity levels. Physical activity is defined as any form of bodily movement that increases energy expenditure, thus playing a role in maintaining energy balance and preventing the risk of excess weight. Purpose: To analyze the relationship between physical activity and nutritional status of students in junior high school. Method: This quantitative research with an analytical observational design employed a cross-sectional approach. The study was conducted from March to July 2025 at Pineleng 2 Public Junior High School, involving 77 respondents in grades VII and VIII. The research instruments included the International Physical Activity Questionnaire (IPAQ) and the SECA height and weight measurement tool. Data were analyzed using univariate and bivariate methods, with Fisher's exact test for correlation between variables. Results: some respondents had active physical activity totaling 69 respondents and for good nutritional status totaling 58 respondents. Conclusion: There is a relationship between physical activity and nutritional status with a p value = 0.019 (p<0.05).   Keywords: Adolescents; Nutritional Status; Physical Activity.   Pendahuluan: Remaja termasuk dalam kelompok yang rentan terhadap masalah gizi. Faktor utama yang melatarbelakangi hal ini adalah masa remaja merupakan periode percepatan pertumbuhan dan perkembangan, yang sering kali diiringi dengan perubahan kebiasaan makan dan pola hidup. Meskipun setiap remaja mempunyai tuntutan yang berbeda, tingkat aktivitas pada usia remaja akan mulai cukup meningkat ketika mendekati usia Sekolah Menengah Pertama. Status gizi remaja dipengaruhi oleh berbagai faktor, antara lain kebiasaan makan, kondisi ekonomi, latar belakang budaya, dan tingkat aktivitas fisik. Aktivitas fisik didefinisikan sebagai segala bentuk gerakan tubuh yang meningkatkan pengeluaran energi, sehingga berperan dalam menjaga keseimbangan energi dan mencegah risiko kelebihan berat badan. Tujuan: Untuk menganalisis hubungan antara aktivitas fisik dan status gizi peserta didik di SMP. Metode: Penelitian kuantitatif dengan desain observasional analitik menggunakan pendekatan cross sectional study. Penelitian dilaksanakan pada Maret–Juli 2025 di SMP Negeri 2 Pineleng dengan melibatkan 77 responden kelas VII dan VIII. Instrumen penelitian meliputi kuesioner International Physical Activity Questionnaire (IPAQ) serta alat ukur tinggi badan dan berat badan merk SECA. Analisis data dilakukan secara univariat dan bivariat, dengan uji hubungan antar variabel menggunakan uji Fisher’s Exact Test. Hasil: Sebagian responden memiliki aktivitas fisik aktif berjumlah 69 responden dan untuk status gizi baik berjumlah 58 responden. Simpulan: Terdapat hubungan antara aktivitas fisik dengan status gizi dengan nilai p = 0.019 (p<0.05).   Kata Kunci: Aktivitas Fisik; Remaja; Status Gizi.